Development of human machine interface (HMI) for power electronics converter - Yu, Hanxi (2016)
The icebreaker is a kind of ship or boat that is specially used for navigating through waters covered by ice. It usually demands high power propulsion drivers to enable shipping directly through thick ice. Nowadays, the medium voltage converter in marine power system, especially for the high power propulsion drivers on the icebreaker are designed for operation of various speed control and lower energy losses. Has been studying since mid-1980s, the technology of multilevel converter has progressed tremendously. One type of it, the Cascaded H-Bridge (CHB) Inverter is highly developed and commercialized. As the result, an even increasing number of companies invest in this area. Rolls-Royce Singapore is one of them. A team from the Rolls-Royce@NTU Corporate Lab launched a project to develop medium voltage converter hardware together with the control algorithm for marine propulsion system in 2014. This study is part of the phase II of the Rolls-Royce project. The purpose of this final year project is to design, develop and implement a Human Machine Interface as an auxiliary service of the medium voltage converter, which is able to communicate with controllers. It allows user to monitor and control the converter. The tool used in this project is C# programming language in Visual Studio Windows Form Application. The hardware is the Z-7010 slave board with the Zynq 7010 AP SoC programmable System-on-Chip.